2016
DOI: 10.1088/1742-6596/745/3/032070
|View full text |Cite
|
Sign up to set email alerts
|

Field synergy analysis of six starts spiral corrugated tube under high Reynolds number

Abstract: Abstract. Coaxial heat exchanger is widely used in air conditioning, refrigeration etc., due to its highly efficient heat transfer performance. Spiral corrugated tube plays an important role in coaxial heat exchanger. In this paper, the numerical model of a six starts spiral corrugated tube and a smooth tube with the same size are developed. The temperature field and the velocity field of their streamline and longitudinal vortex are investigated respectively. Then, their heat transfer and pressure drop perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The results showed that the heat transfer coefficient was the highest when the pitch ratio was 3.75; when the pitch ratio was 4.5, the comprehensive heat transfer performance was the best. Qian et al [5] used numerical simulation to study the heat transfer and resistance performance of six-start spirally corrugated tubes and compared them with smooth tubes from the perspective of their synergy angle. Their research showed that the heat transfer performance of the spirally corrugated tube was better than that of the smooth tube, and that the friction coefficient also increased.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the heat transfer coefficient was the highest when the pitch ratio was 3.75; when the pitch ratio was 4.5, the comprehensive heat transfer performance was the best. Qian et al [5] used numerical simulation to study the heat transfer and resistance performance of six-start spirally corrugated tubes and compared them with smooth tubes from the perspective of their synergy angle. Their research showed that the heat transfer performance of the spirally corrugated tube was better than that of the smooth tube, and that the friction coefficient also increased.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [30][31][32], the effects of pitch and corrugation depth on heat transfer performance and flow resistance characteristics inside a six-start spirally corrugated tubes have been studied numerically by calculating the Nusselt number and flow resistance coefficient. However, for the heat transfer and flow resistance on the shell side research, investigations are missing.…”
Section: Introductionmentioning
confidence: 99%